Drone distribution model for emergency medicine distribution to reduce delivery time and costs: case of the Peruvian health sector - Jenss Senador, David Kevin (2024)
The lack of adequate infrastructure for most of the roads and routes in Peru, has generated a saturation of the roads and longer transport times, which affects the state health sector presenting frequent situations of shortages of medicines for urgent and emergency cases nationwide due to various factors such as the use of ambulances used for the delivery of medicines in a very congested road infrastructure. This research proposes an emergency medicine distribution model to reduce delivery time and costs using drones (remotely piloted unmanned aerial vehicles). The distribution of medicines to thirteen medical posts using 4 ambulances in the northern area of Lima was analyzed and the results were compared with the distribution of medicines using 21 drones, providing care to 313,248 emergency cases, demonstrating the reduction of delivery times and costs. It can be concluded that the use of drones as a substitute in the distribution of emergency medications and medical items is a faster and 22 times less expensive means than traditional distribution using ambulances or distribution trucks, demonstrating that the model is viable to be implemented in the northern area of Lima.